Exploring the Aspiration of Seeing a Buddha in Pāli Buddhism - Kumar, Bimalendra (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
In Pali Buddhism, the aspiration to see a Buddha is a profound and multifaceted theme that encompasses spiritual longing, devotion, and the pursuit of enlightenment. This aspiration is rooted in the belief that encountering a Buddha, particularly Gotama Buddha, the historical founder of Buddhism, offers a unique opportunity for spiritual growth and liberation. The desire to see a Buddha is often linked to the cultivation of faith, wisdom, and merit, which are essential components of the Buddhist path. There is the aspiration of seeing a Buddha or the Metteyya in the future. According to the second chapter Sumedhakathā (Bv II 59) in the Bv, there are eight dhammas (aṭṭhadhammasamodhānā), which are necessary to be resolved as aspirations for becoming Buddha. In the commentary of Majjhimanikāya, it is said that “These are the causes for the accomplishment of the resolution. In this paper there is an endeavour to make interpretation of these eight dhammas (aṭṭhadhammasamodhānā), which are necessary to be resolved as aspirations on the basis of Pali texts and its commentarial literatures. This exploration will delve into the significance of the aspiration to see a Buddha in Pali Buddhism, examining its role in the spiritual journey of practitioners and its relationship to key Buddhist concepts such as faith, wisdom, and liberation. By understanding this aspiration, we can gain deeper insights into the nature of Buddhist devotion and the path to enlightenment.